Evaluation of enteral and parenteral hyaluronic acid in induced ischemic skin flaps in rats: a double-blinded and randomized study - Gallina, Marina Frazatti [UNESP]; Dos Santos, Ivan Felismino Charas; da Silva, Bruna Martins; Pereira, Guilherme Cirino Coelho [UNESP]; Gushiken, Lucas Fernando Sérgio; Pellizzon, Claudia Helena [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Schons, Sandro de Vargas; Silva, Fernando Do Carmo; Sena, Kamile Daguano; Rosa, Vinicius Dos Santos (My University, 2024)
Purpose: To evaluate exogenous hyaluronic acid (HA) derived from bacterial fermentation through enteral and parenteral routes in ischemic skin flaps induced in rats, using clinical and histological exams; and interleukins (IL) as tissue inflammatory biomarkers. Methods: Sixty-four male adults Wistar rats with ischemic skin flaps on the dorsum were randomized into four groups, based on the treatment protocol: subcutaneous administration of saline solution (0.9%) (GI); oral administration of distilled water (GII); subcutaneous administration of HA (0.3%) (GIII); and oral administration of HA (1%) (GIV). Flaps of all groups were comparable regarding clinical and macroscopic evaluation, histological examination, pro-inflammatory cytokines (IL-1β, IL-6, and tumor necrosis factor-α) and anti-inflammatory cytokine IL-10. Results: A lower percentage of necrosis was identified in flaps treated with subcutaneous administration of HA (0.3%). The pro-and anti-inflammatory cytokines, epidermis thickness, blood vessels, and inflammatory cells showed statistically significant inter-group and intra-group differences (p < 0.05). Conclusion: High molecular HA (1,400 ~ 2,000 kDa) administrated by subcutaneous or oral route exhibited beneficial effects in ischemic skin flaps of rats. However, subcutaneous administration of HA (0.3%) showed better results in terms of the percentage of necrosis and epithelialization.
Keywords: Hyaluronic Acid; Inflammatory Cytocines; Surgery, Plastic; Wound Healing